Crushing analysis and multiobjective optimization design for rectangular unequal triple-cell tubes subjected to axial loading. (August 2017) - Shen, Wen; Gu, Xianguang; Jiang, Ping; Hu, Jinfang; Lv, Xiaojiang; Qian, Lijun
Abstract: Multi-cell thin-walled tubes have proven to be better in energy absorption than plain square tubes subjected to axial compression. Therefore, square multi-cell structures have been extensively utilized as energy absorbers in automobiles. This paper provides an investigation on the crashworthiness of rectangular single-, double- and triple-cell columns under axial loading and an optimization design of rectangular unequal triple-cell tubes. First, a theoretical solution is derived for the mean crushing force (MCF) of tubes with unequal triple-cell configuration. Second, quasi-static crushing experiments and finite element analyses (FEA) are conducted on single-, double- and unequal triple-cell columns. Theoretical predictions compare well with experimental and numerical data, and all results show that the triple-cell tubes exhibit the best crashworthiness among all the samples. Third, in order to study effects of wall thickness distribution and the layout of internal ribs on crashing behavior, multiobjective optimization design is implemented combining Radial Basis Function (RBF) model with Non-dominant sorting Genetic Algorithm II (NSGA-II). The optimal solution obtained from Pareto frontier indicates that unequal triple-cell tube with appropriate thickness distribution and arrangement of internal ribs is superior in energy absorption to initial design. Highlights: Theoretical predictions compare well with experimental and numerical data. All results show that the triple-cell tubes exhibit the best crashworthines. The effects of the thickness of each plate and arrangements of internal ribs are investigated.